2007
DOI: 10.1523/jneurosci.4239-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Genetic and Environmental Factors in aDrosophilaParkinsonism Model

Abstract: Catastrophic loss of dopaminergic neurons is a hallmark of Parkinson's disease. Despite the recent identification of genes associated with familial parkinsonism, the etiology of most Parkinson's disease cases is not understood. Environmental toxins, such as the herbicide paraquat, appear to be risk factors, and it has been proposed that susceptibility is influenced by genetic background. The genetic model organism Drosophila is an advantageous system for the identification of genetic susceptibility factors. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
216
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(237 citation statements)
references
References 48 publications
17
216
0
Order By: Relevance
“…5B). The sensitivity of ple heterozygous mutant flies to the exposure of 1-octen-3-ol likely reflects the modulatory function of dopamine in the pathways governing survival and locomotory behavior, as seen previously with paraquat exposure (22).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…5B). The sensitivity of ple heterozygous mutant flies to the exposure of 1-octen-3-ol likely reflects the modulatory function of dopamine in the pathways governing survival and locomotory behavior, as seen previously with paraquat exposure (22).…”
Section: Discussionmentioning
confidence: 52%
“…Pharmacological inhibition of TH, catecholamine uptake, and α-adrenoreceptor antagonists at 1 mM concentration results in failure of viable progeny whereas lower concentration (0.1 mM) significantly delayed the development, indicating the essential function of catecholamines in Drosophila development and viability (50). Drosophila tyrosine hydroxylase is encoded by the pale locus (51), and mutations in the pale gene result in decreased dopamine pools in adult heads, even in the heterozygous state (22). Compared with wild type, ple mutants showed increased susceptibility toward various types of stress, including the dopaminergic toxicant paraquat, indicating that dopamine functions as a key element in the stress response (22,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paraquat (PQ) (1,1-dimethyl-4-4-bipyridynium dichloride) (PQ), is widely used as herbicide. In vivo studies employing Drosophila melanogaster [5], Rattus norvegicus [6] and Mus musculus [7] have revealed that PQ is neurotoxic which affects dopaminergic neurons. The toxicity of PQ is a consequence of generation of ROS mainly hydrogen peroxide and hydroxyl radical [8].…”
Section: Introductionmentioning
confidence: 99%